Pendampingan Pengurusan Perijinan Spp-Irt Pada Ukm Candi Mas Desa Bancong, Kecamatan Wonoasri, Kabupaten Madiun - Hery Hermawan; Sulistya Eviningrum (Universitas Merdeka Madiun, 2018)
Small and Medium Enterprises (SMEs) become one of the supporters of national economic resilience. One of the obstacles to the development of SME Candi Mas is not yet taken care of or the existence of Certificate of Household Food Production Industry (SPP-IRT). Therefore, it is necessary to assist the handling of Licensing of SPP-IRT in SME Candi Mas Bancong village, Wonoasri sub-district, Madiun district. The timing of this community service is from May to October 2017. The results are: 1) The completion of counseling and facilitation of licensing arrangement of SPP-IRT. 2) Provision of Temporary Permit on Household Food Production Certification (SPPIRT) Number: 094/2326 / 402.102 / 2017 on June 9, 2017 for Mas Candi Company, product coverage: brem products, pecel sambel, one cake, and tempe chips Madiun District Health Office on June 9, 2017. 3) The obtaining of Food Safety Counseling Certificate Number: 914/351/17 was given to Fekodin (Owner of SME Candi Mas) from Madiun District Health Office on October 31, 2017. 4) Obtaining Certificate Household Food Production (SPPIRT) Number: 2153519010914 - 22 for IRT Candi Mas from Madiun Regency Health Office, product range: brem products, pecel sambel, one cake, and tempe chips, on 31 October 2017.